Acceptability of a high-protein Mediterranean-style diet and resistance exercise protocol for cardiac rehabilitation patients: Involving service users in intervention design using a mixed-methods participatory approach - Kirwan, Richard; Newson, Lisa; McCullough, Deaglan; Butler, Tom; Davies, Ian G.; Perez de Heredia, Fatima (Frontiers in Nutrition, 2023)
Background Current cardiac rehabilitation (CR) practices focus on aerobic-style exercise with minimal nutrition advice. This approach may not be optimal for CR patients with reduced muscle mass and elevated fat mass. Higher protein, Mediterranean-style diets combined with resistance exercise (RE) may improve muscle mass and reduce the risk of future cardiovascular events, although such an approach is yet to be trialed in a CR population. Objective We explored patient perspectives on the proposed design of a feasibility study. Patients reflected on the acceptability of a proposed high-protein Mediterranean-style diet and RE protocol, emphasizing research methodology and the acceptability of the proposed recipes and exercises. Design We applied quantitative and qualitative (mixed methods) approaches. The quantitative approach involved an online questionnaire (n = 40) regarding the proposed study methodology and relevance. A subset of participants (n = 12) received proposed recipe guides and were asked to prepare several dishes and complete an online questionnaire regarding their experience. Another subset (n = 18) received links to videos of the proposed RE and completed a questionnaire regarding their impressions of them. Finally, semi-structured interviews (n = 7) were carried out to explore participants’ impressions of the proposed diet and exercise intervention. Results Quantitative data indicated a high level of understanding of the intervention protocol and its importance within the context of this research. There was a high degree of willingness to participate in all aspects of the proposed study (>90%). The trialed recipes were enjoyed and found to be easy to make by a majority of participants (79 and 92.1%, respectively). For the proposed exercises 96.5% of responses agreed they would be willing to perform them and, 75.8% of responses agreed they would enjoy them. Qualitative analysis revealed that participants viewed the research proposal, diet, and exercise protocol in a positive light. The research materials were considered appropriate and well explained. Participants suggested practical recommendations for improving recipe guides and requested more individual-focused exercise recommendations, and more information on the specific health benefits of the diet and exercise protocols. Conclusion The study methodology and the specific dietary intervention and exercise protocol were found to be generally acceptable with some suggested refinements.